2014
DOI: 10.20510/ukjpb/2/i5/91149
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polymer Concentration for Designing of Oral Matrix Controlled Release Dosage Form

Abstract: Patient’s compliance can be enhanced by using extended release drug delivery systems which allow decreasing the number of daily doses, and helping to maintain uniform drug levels and increase the safety margin for high-potency drugs. Hydroxypropyl methylcellulose (HPMC) is the most commonly used hydrophilic polymer for the preparation of oral controlled drug delivery systems. This research was conducted with the aim of  developing matrix based oral controlled release tablets for the drug diclofenac sodium usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…indicates the Fickian diffusion is the mechanism of CA release [61]. The similar values of the n exponent in NC (0.33) and NE (0.23) indicated that chitosan on the surface of NC did not affect the CA release behavior compared to the NE.…”
Section: Discussionmentioning
confidence: 82%
“…indicates the Fickian diffusion is the mechanism of CA release [61]. The similar values of the n exponent in NC (0.33) and NE (0.23) indicated that chitosan on the surface of NC did not affect the CA release behavior compared to the NE.…”
Section: Discussionmentioning
confidence: 82%
“…This indicates that the formulation followed non-Fickian type drug release. The reason could be attributed to the increase in molecular rearrangement of polymeric chains and drug polymer interaction as the solvent diffuses in the nanoparticles [ 38 , 39 ]. Therefore, this could be useful in cancer therapy for the targeted delivery of the drug and also for the prolonged period of time [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the release exponent n value in both conditions was less than 0.45, the result confirms the Fickian diffusion type of release of Diosgenin from the PCL-F68-D-NPs. Earlier, it was reported that the increase in drug-polymer interaction and molecular rearrangement of polymer chains can cause slower diffusion and release as the solvent diffuses into the nanoparticles, which is useful for targeted delivery [60,61].…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%